(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Chorna O. V. Quality management and quality management in education. The article is devoted to the analysis of problem of education quality in view of its correspondence to the demands of modern society. To the author`s opinion the way to the improvement of it must go through the optimization of quality management at the university and the introduction of quality management system based on the family of international standards ISO 9000.